SEM analysis for tourist expenditure in an emerging country - Guillén Uyen, Jorge (2019)
The following study attempts to examine the relationship between consumer preferences and expenditure in a Structural Equation Model (SEM) framework. We use data from a survey applied in an emerging country like Peru. There were 6 772 respondents classified by sex, country of residence, education level, and age. The foreign respondents specified their motives and preferences to travel as well as money spent. The SEM technique permit to find a relationship between the latter variables. This assessment is relevant for tourism policymakers since it will help to find the main drivers of expenditure by foreign visitors within an emerging country. Our study permitted us to identify the motives to visit: leisure, business and education, and others as main drivers of touristic expenditure.